Guinness World Records, 2020 - Glenday, Craig (London : Guinness World Records Limited, 2019)
Presents the biggest, smallest, fastest, longest, and other record setters for 2019 in the categories of space, Earth, animals, humans, fantastic feats, science and technology, arts and media, and sports.
Includes index.
Young Adult
Keywords: Curiosities and wonders; World records